Germline gain‐of‐function MMP11 variant results in an aggressive form of colorectal cancer. Issue 2 (3rd October 2022) - Martin‐Morales, Lorena; Manzano, Sara; Rodrigo‐Faus, Maria; Vicente‐Barrueco, Adrian; Lorca, Victor; Núñez‐Moreno, Gonzalo; Bragado, Paloma; Porras, Almudena; Caldes, Trinidad; Garre, Pilar; Gutierrez‐Uzquiza, Alvaro
Abstract: Matrix metalloproteinase‐11 (MMP11) is an enzyme with proteolytic activity against matrix and nonmatrix proteins. Although most MMPs are secreted as inactive proenzymes and are later activated extracellularly, MMP11 is activated intracellularly by furin within the constitutive secretory pathway. It is a key factor in physiological tissue remodeling and its alteration may play an important role in the progression of epithelial malignancies and other diseases. TCGA colon and colorectal adenocarcinoma data showed that upregulation of MMP11 expression correlates with tumorigenesis and malignancy. Here, we provide evidence that a germline variant in the MMP11 gene (NM _ 005940: c.232C>T; p.(Pro78Ser)), identified by whole exome sequencing, can increase the tumorigenic properties of colorectal cancer (CRC) cells. P78S is located in the prodomain region, which is responsible for blocking MMP11's protease activity. This variant was detected in the proband and all the cancer‐affected family members analyzed, while it was not detected in healthy relatives. In silico analyses predict that P78S could have an impact on the activation of the enzyme. Furthermore, our in vitro analyses show that the expression of P78S in HCT116 cells increases tumor cell invasion and proliferation. In summary, our results show that this variant could modify the structure of the MMP11 prodomain, producing a premature or uncontrolled activation of the enzyme that may contribute to an early CRC onset in these patients. The study of this gene in other CRC cases will provide further information about its role in CRC development, which might improve patient treatment in the future. Abstract : What's new? Matrix metalloproteinases have a tremendous capacity to degrade extracellular matrix proteins. While their activity has been closely associated with the invasive nature of malignant solid tumors, including colorectal cancer, their role in the carcinogenesis of colorectal adenomas remains unclear. Here, the authors unveil an MMP11 variant able to produce a premature or uncontrolled activation of the MMP11 enzyme that may contribute to early disease onset in colorectal cancer patients. The identification of this new variant may facilitate the earlier detection of new tumors as they develop or become malignant in colorectal cancer patients.